Effects of dietary combination of chromium and biotin on growth performance, carcass characteristics, and oxidative stress markers in heat-distressed Japanese quail - Onderci, M; Şahin, Kazım; Şahin, Nurhan; Cikim, G; Vijaya, J; Küçük, Ömer (Springernature, 2005)
Environmental stress causes adverse effects in performance and antioxidant status of poultry. Dietary chromium supplementation promotes the growth rate and feed efficiency of growing poultry and these beneficial effects of chromium appear to be greater under stress. Biotin, a member of the vitamin B complex, is involved in the metabolism of carbohydrates, fats, and proteins. In a previous experiment, we examined the effects of chromium picolinate (CrPic) as a chromium source in birds subjected to high environmental temperature and the data showed that supplementation with CrPic ameliorated the deletorious effect of stress. The study was conducted to determine the effects of a supplementation of combination of CrPic and biotin (Diachrome (TM)) on performance, carcass characteristics, levels of oxidative stress markers, serum cholesterol, and glucose concentrations in Japanese quail (Coturnix coturnix japonica) exposed to high ambient temperature of 34 C. Two hundred forty Japanese quail (10 d old) were randomly assigned to 8 treatment groups consisting of 10 replicates of 3 birds. The birds were kept in a temperature-controlled room at 22 degrees C (thermo-neutral [TN] groups) or 34 C (for 8 h/d; 09.00 AM to 05.00 PM; heat-stress [HS] groups). Birds were fed either a basal (control) diet (TN and HS) or the basal diet supplemented with either 1, 2, or 4 mg of Diachrome/kg of diet. Heat exposure decreased performance when the basal diet was fed (p = 0.001). Diachrome supplementation increased feed intake (p = 0.001), body weight (p = 0.05), feed efficiency (p = 0.01), and carcass traits (p <= 0.05) variables linearly in birds reared under HS conditions. Serum vitamin C (p = 0.05) and vitamin E (p = 0.03) concentrations increased, whereas malondialdehyde (MDA) levels in serum and the liver (p = 0.01), thigh muscle (p = 0.05), and serum cholesterol and glucose concentrations (p = 0.05) decreased in supplemented birds reared at a high temperature. It should be noted that when birds were kept at the thermo-neutral temperature, Diachrome supplementation did not affect (p > 0.05) the variables measured, with the exception of a reduction in serum cholesterol and glucose. Results of the present study suggest that Diachrome can be considered a protective dietary supplement by reducing the negative effects of high environment temperature on performance and oxidative stress in quail.
Keywords: chromium; biotin; heat stress; meat quality; quails